Gravity field due to a homogeneous oblate spheroid: Simple solution form and numerical calculations - HVOŽDARA, Milan; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2011)
We present a simple derivation of the interior and exterior gravitational potentialsdue to oblate spheroid and also its gravity field components by using the fundamentalsolution of the Laplace equation in oblate spheroidal coordinates. Application ofthe method of separation of variables provides an expression for the potential in terms ofoblate spheroidal harmonics of degree n = 0, 2. This solution is more concise and suitablefor the numerical calculations in comparison with infinite series in spherical harmonics.Also presented are the computations in the form of potential isolines inside and outsidethe spheroid, as well as for the gravity field components. These reveal some interestingproperties of the gravity field of this fundamental geophysical body useful for the appliedgravimetry.